Training and mentoring of Posyandu cadres based on behavior change in an effort to prevent stunting in Mulyoagung village, Dau sub-district, Malang district - Juli Astutik; Budi Suprapto; Zaenal Abidin (Journal of Community Service and Empowerment)
Stunting remains a major public health issue in Indonesia, with a prevalence of 37% in 2013 and 30.8% in 2018, affecting approximately 8.4 million children under five. This condition is not limited to children from poor families but also affects those from well-off households. The causes of stunting are multidimensional, involving not only nutritional deficiencies in pregnant women and toddlers but also high-risk behaviors related to parenting and health practices. This community service program aimed to enhance the capacity of posyandu (integrated health post) cadres in stunting prevention through a behavior change approach. The methods applied included counseling, training, and mentoring for cadres in Mulyoagung Village, Dau Sub-district, Malang District. The outcomes demonstrated a significant improvement in the cadres’ understanding of stunting, its causes, and impacts. Participants also gained insights into the importance of behavior change education in preventing stunting. Feedback indicated increased mastery of practical prevention strategies, and cadres were able to apply and disseminate the training materials in their community in an integrated and sustainable manner. In conclusion, training and mentoring based on behavior change effectively empowered posyandu cadres in stunting prevention efforts.